Cyano-ambivalence: Spectroscopy and photophysics of [Ru(diimine)(CN-BR3)4]2− complexes. (15th September 2020) - Ngo, Danh X.; Del Ciello, Sarah A.; McNicholas, Brendon J.; Sanders, Brian C.; Fajardo, Javier; Gray, Harry B.; Winkler, Jay R.
Graphical abstract: Abstract: The UV–visible absorption and luminescence spectra of [Ru(diimine)(CN)4 ] 2− derivatives have been tuned over wide ranges through variations in solvent, substituents on the diimine ligand, and boronation of the cyanide ligands. Trifluoromethyl substitution at the 4 and 4′ positions of the diimine induces red shifts in metal-to-ligand charge-transfer (MLCT) absorption and luminescence bands. Boronation of the cyanide ligands produces substantial blue shifts in MLCT energies. The combination of diimine trifluoromethylation and cyanide boronation produces MLCT blue shifts that are about 75% as large as those produced by boronation alone.